Familial Dysbetalipoproteinemia, Diagnosis and Management: A Short Review (Iraqi Journal of Medical Sciences, 2023)
Papers on the familial lipid disorder, dysbetalipoproteinemia (FD), appeared in early seventies of the last century describing the combined elevation in total cholesterol (TC) and triglycerides (TG) in the blood of affected individuals, which is associated with mutations in the apo-lipoprotein E (Apo E) gene. Different methods and measurements for diagnosis and consequent treatment of these cases had been suggested. Stress was put on the E2/E2 homozygotes, Apo B and non-high density lipoprotein cholesterol as the main obvious manifestations of the disease, with a big variation in the results among different workers. This short review will present most of these variations in nature, diagnosis and management of FD, with a reference to a recent Iraqi work on this subject.Keywords: Dysbetalipoproteinemia, mixed hyperlipidemia, Apo E, Apo B, non-HDL cholesterol, lipid lowering drugsCitation: Al-Shamma GAA. Familial dysbetalipoproteinemia, diagnosis and management: A short review. Iraqi JMS. 2023; 21(2): 189-192. doi: 10.22578/IJMS.21.2.6
Keywords: Dysbetalipoproteinemia; mixed hyperlipidemia; Apo E; Apo B; nonHDL cholesterol; lipid lowering drugs